Perfil epidemiológico, clínico, laboratorial e imagenológico de los pacientes pediátricos diagnosticados de dengue con signos de alarma o dengue grave en el Hospital Regional de Loreto; 2020 - Nakandakari Gomez, Mayron David (2022)
Objectives: To evaluate the epidemiological, clinical, laboratory and imaging profile of pediatric patients diagnosed with dengue with warning signs and severe dengue in a hospital in the Peruvian Amazon; 2020. Methodology: Observational, descriptive, cross-sectional and retrospective research. It will study the total of pediatric patients diagnosed with dengue with warning signs or severe dengue at the Regional Hospital of Loreto from January to December 2020. A secondary source such as medical history will be used to collect the data. The analysis shall be quantitative. With a 95% confidence interval and a significance level of p<0.005. Expected results: Among the results, it is expected that the vast majority of patients come from the outskirts of the city of Iquitos, that the predominant form of clinical presentation will be that of dengue without warning signs, that leukopenia, decreased platelets and hemoconcentration will be frequently evidenced in the blood count, and that radiological examinations such as ultrasound or radiography will determine findings indicative of plasma extravasation.